Bank Guarantee as a Means of Securing Contract Performance under the Law of the Republic of Serbia - Varađanin, Tanja; Stanković, Marko; Stefanović, Nenad (Naše gospodarstvo/Our economy, 2025)
Bank guarantees are the most widely used instrument to secure contract performance in commercial law, both nationally and internationally. They are commonly employed in sales contracts and during the execution of foreign investment projects. Establishing a bank guarantee is prompt and effective falling under neutral banking operations. As the number of business entities has grown significantly, there has been a corresponding increase in commercial contracts requiring secured performance. Despite the advantages of swift transactions at both levels, business entities face economic and legal risks that drive them to secure contracts most effectively to protect their interests and achieve their business goals. In this context, the bank is essential in fostering successful business collaborations. Given the importance and complex nature of bank guarantees in today’s legal transactions, this paper examines current issues and challenges related to the key aspects of bank guarantees as a means to secure contract performance, including their efficiency and speed in enforcement, along with their advantages and disadvantages, with particular reference to judicial decisions and electronic bank guarantees in light of innovative technologies. It reviews existing statutory provisions and provides a comparative analysis across various levels. The paper focuses on eliminating uncertainties surrounding the bank guarantee institution to promote more secure business practices.